2014
DOI: 10.1161/jaha.114.001089
|View full text |Cite
|
Sign up to set email alerts
|

Early Discharge After Primary Percutaneous Coronary Intervention: The Added Value of N‐Terminal Pro–Brain Natriuretic Peptide to the Zwolle Risk Score

Abstract: BackgroundThe Zwolle Risk Score (ZRS) identifies ST‐elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (PPCI) eligible for early discharge. We aimed to investigate whether baseline N‐terminal pro–brain natriuretic peptide (NT‐proBNP) is also able to identify these patients and could improve future risk strategies.Methods and ResultsPPCI patients included in the Ongoing Tirofiban in Myocardial Infarction Evaluation (On‐TIME) II study were candidates (N=861).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…Previous studies highlighted that, in patients with STEMI, NT-proBNP, drawn within 24 hours of the onset of chest pain, is more accurate in predicting mortality than the TIMI risk score 26. Indeed, our group recently revealed that baseline NT-proBNP values predict 30-day mortality in patients with STEMI, treated with primary PCI independently and even more strongly than the Zwolle risk score alone 27. However, in patients with STEMI the prognostic value of NT-proBNP on long-term, 5-year mortality outcomes to date has never been reported.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies highlighted that, in patients with STEMI, NT-proBNP, drawn within 24 hours of the onset of chest pain, is more accurate in predicting mortality than the TIMI risk score 26. Indeed, our group recently revealed that baseline NT-proBNP values predict 30-day mortality in patients with STEMI, treated with primary PCI independently and even more strongly than the Zwolle risk score alone 27. However, in patients with STEMI the prognostic value of NT-proBNP on long-term, 5-year mortality outcomes to date has never been reported.…”
Section: Discussionmentioning
confidence: 87%
“…In patients with STEMI, previous MI, door to balloon time, the presence of diabetes, anemia, chronic renal failure, and ejection fraction on admission are the main predictors of mortality. Risk scores such as TIMI, GRACE, PAMI, Zwolle, or CADILLAC are commonly applied as mortality indicators (3)(4)(5)(6)13,14). Beyond clinical data, angiographic data are also used to predict the longterm prognosis, such as the SYNTAX score (15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, risk stratification is essential for clinical decision and management. Various risk scores such as Thrombolysis in Myocardial Infarction (TIMI), GRACE, and ZWOLLE have been applied (3)(4)(5). Besides angiographic variables, clinical data, such as the presence of anemia and renal impairment, are independent risk factors for in-hospital cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1). Recently, we demonstrated that the predictive accuracy of the ZRS was improved by adding baseline NT-proBNP [12]. In this report we studied the value of NT-proBNP measurement at different timepoints over and beyond the ZRS.
Fig.
…”
Section: Introductionmentioning
confidence: 99%